Features of Surface Layer Structure of VT23 Titanium Alloy under Bombardment with Copper Ions; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Kalashnikov M. P. Mark Petrovich; Fedorishcheva M. V. Marina Vladimirovna; Sergeev V. P. Viktor Petrovich; Neyfeld V. V. Vasilii; Popova N. A. Natalya (2015, 2015)
Title screen